A greener tetraphenylporphyrin synthesis and metallation: an undergraduate teaching experiment. Issue 1 (2nd January 2023) - Nitka, Matthew A.; Zerbee, Katarina E.; Dee, Julianne M.; Cranswick, Matthew A.; Zovinka, Edward P.; De Backere, John R.
ABSTRACT: While porphyrin-related syntheses have become classic experiments in the undergraduate curriculum, traditional syntheses of the free-base meso -tetraphenylporphyrin (H2 TPP) and its metallated derivatives can be energy-intensive, use hazardous solvents, and generate appreciable amounts of waste. In an attempt to make the synthesis of H2 TPP and its metallated derivatives (MTPP where M = metal) better aligned with the principles of green chemistry, we optimized a microwave-assisted, microscale synthesis of H2 TPP and alternative routes toward the metallation of H2 TPP including solvent-substituted reflux and mechanochemical syntheses for the undergraduate teaching laboratory. The greenness of these syntheses were evaluated using various green metrics and qualitative comparison to previously reported syntheses.